Leasing and Secondary Markets: Theory and Evidence from Commercial Aircraft. - Gavazza, Alessandro (Journal of Political Economy, 2011)
I develop a model of costly capital reallocation to understand how leasing reduces trading frictions. Leased assets trade more frequently and produce more output than owned assets because (1) high-volatility firms are more likely to lease than low-volatility firms and (2) firms shed leased asssets faster than owned assets amid productivity shocks because of lower transaction costs. Commercial aircraft data show that leased aircraft have holding durations 38 percent shorter and fly 6.5 percent more hours than owned aircraft. These differences arise primarily because when profitability declines, carriers keep owned aircraft and return leased aircraft, which lessors redeploy to more productive operators. Reprinted by permission of the publisher.